Analisis Gender Atas Penambahan Beban Administrasi Klaim PTKP Wanita Kawin: (Komparasi Hukum Indonesia Dengan Singapura) (RechtJiva, 2025)
The problem raised in this thesis is the legal conflict of adding the administrative burden of claiming non-taxable income for married women as the head of the family in Law No. 36 of 2008 on Income Tax (Income Tax Law) along with its derived regulations and amendments that are contrary to the principles of justice and the principles of equality in the 1945 Constitution and the main principles of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). This research method is normative juridical with statutory, comparative, conceptual and historical approaches analyzed using grammatical, systematic and comparative methods of interpretation. This research concludes that the Income Tax Law, along with its derived regulations and amendments, is demonstrably gender-inappropriate because it does not fulfill the principles of justice and equality guaranteed by the 1945 Constitution and CEDAW. The Income Tax Law has created procedural inequality between married men and women in claiming the PTKP component. Comparative analysis shows that Indonesia's income tax provisions do not fully comply with the three main principles of CEDAW, unlike Singapore which has fully complied with them. For this reason, this thesis recommends tax law reform to deconstruct norms that are not yet gender sensitive.